Point-of-care surface plasmon resonance biosensor for stroke biomarkers - Koh, Brescia Rui Wen (2019)
Stroke is the second most common cause of death. Stroke is a time sensitive disease and reducing the time-to-treatment can increase patient’s access to treatment and therefore save patients’ lives. Recent studies have shown that blood-based biomarkers measurement may assist in monitoring stroke risk and prognosis. By monitoring specific stroke biomarker, stroke can be characterized and risk can be predicted thereby reducing the time-to-treatment. In this project, a point-of-care surface plasmon resonance (SPR) biosensor is developed for the detection of stroke biomarkers (NT-proBNP and S100B) using SPR Module (PhotonicSys SPR H5). SPR is a quantum electromagnetic phenomenon which emerges from the interaction of light with free electrons at a metal-dielectric interface. The novelty of this project is in the substrate as well as the reading methodology. The antibody was bonded onto the novel substrate via covalent bond for specific detection and tested with water samples. Stroke biomarkers (NT-proBNP and S100B) were detected on two substrate (Silicon Dioxide and Gold) in a detection range of 0.10 ng/mL to 10.00 ng/mL. The biosensor demonstrated a clinically relevant limit-of-detection in ng/mL range.